ANALISIS PENGARUH HARGA (PRICE), SUASANA TOKO (STORE ATMOSPHERE), DAN CITA RASA (TASTE) TERHADAP KEPUASAN PELANGGAN TOKO KOPI SEDUH PESANGGRAHAN JAKARTA SELATAN - Deci Rahakbauw, Oktovina; Nugraha , Renalda (Management Research and Business Journal, 2024)
This research aims to determine the influence of the variables Price, Store Atmosphere, and Taste on Customer Satisfaction of the Pesanggrahan Brewed Coffee Shop, South Jakarta. Research data sources are data sources needed to conduct research. These data sources can be obtained either directly, called primary data or indirectly or called secondary data related to the research object. Meanwhile, the types of data used in this research are primary data and secondary data. The population in this study were visitors who drank coffee at the Pesanggrahan Seduh Coffee Shop, South Jakarta. This research uses an accidental sampling technique which aims to obtain samples by chance to be more efficient in sample collection. To take the number of samples using the Slovin formula. The analytical method used in this research is multiple linear regression which is used to test the influence of Price, Store Atmosphere and Taste which are independent variables on Customer Satisfaction which is the dependent variable. Data processing in this research used the Statistical Program for Social Science (SPSS) version 25.0 for Windows. From the results of the t test analysis with a significance level of 5%, it shows that the variables Price, Store Atmosphere, and Taste have a positive and significant effect on Customer Satisfaction. The results of the F test analysis of the variables Price, Store Atmosphere and Taste have a positive and significant effect on Customer Satisfaction. The predictive ability of the three independent variables (Price, Store Atmosphere, and Taste) on the dependent variable (Customer Satisfaction) in this research is 66.5% while the remaining 33.5% is explained by other variables outside the research model.